2019
DOI: 10.1002/jclp.22902
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and behavioral effects of interpersonal validation: A multilevel approach to examining a core intervention strategy among self‐injuring adolescents and their mothers

Abstract: Objective The current study examined how teaching an interpersonal validation‐oriented skill from dialectical behavior therapy affects behavioral and biological indices of self‐inflicted injury (SII) risk among self‐injuring adolescents and their mothers (n = 30 dyads), and typical control mother–daughter dyads (n = 30). Method Behavioral indicators of family functioning (e.g., cohesion, coercion, and invalidation) and a physiological index of emotion dysregulation (respiratory sinus arrhythmia [RSA]) were exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 66 publications
(94 reference statements)
3
28
0
Order By: Relevance
“…Since up to 90% of children with ED meet criteria for a categorized disorder (441), a number of treatments are available for treating the primary disorder. Most therapies also help in improving ED (91,100,164,210,258,430,432,(445)(446)(447)(448)(450)(451)(452)(453)(454)(455)(456)(457). Only the Light Therapeutic Procedure (447), and the Emotion Regulation Training (ERT) for adolescents with BPD (455) showed no improvement (for details, see Tables 1, 2).…”
Section: Preventionmentioning
confidence: 99%
“…Since up to 90% of children with ED meet criteria for a categorized disorder (441), a number of treatments are available for treating the primary disorder. Most therapies also help in improving ED (91,100,164,210,258,430,432,(445)(446)(447)(448)(450)(451)(452)(453)(454)(455)(456)(457). Only the Light Therapeutic Procedure (447), and the Emotion Regulation Training (ERT) for adolescents with BPD (455) showed no improvement (for details, see Tables 1, 2).…”
Section: Preventionmentioning
confidence: 99%
“…To date, limited research has assessed how people who self-injure subjectively and physiologically respond to emotional challenge in real-time. The findings of these studies are mixed; some have found a difference in subjective and/or physiological responding to emotional challenge by self-injury status (e.g., Crowell et al, 2005Crowell et al, , 2008Kaufman et al, 2019;Nock & Mendes, 2008), whereas others have not (e.g., Allen et al, 2019;Davis et al, 2014;Glenn et al, 2011;Kaess et al, 2012;Tatnell et al, 2018). These mixed results across and within subjective and physiological response channels may reflect differences in mood induction methods or how NSSI was operationalised (e.g., 'lifetime NSSI history' compared to 'past-year history'; Nock & Mendes, 2008;Tatnell et al, 2018).…”
Section: The Problemmentioning
confidence: 99%
“…Unfortunately, not all studies which experimentally induced emotion among people with and without a history of self-injury are able to inform our understanding of emotional responding in self-injury. First, several studies failed to include a baseline measure of emotion, either in general (Kim et al, 2015), or for a specific emotional channel (e.g., behavioural responding; Kaufman et al, 2019;Nock & Mendes, 2008). Without a baseline comparison, it is unclear whether any difference by self-injury status is due to a difference in reactivity to emotion or a greater basal level response in general.…”
Section: Responding To Emotional Challenge Manipulationsmentioning
confidence: 99%
See 2 more Smart Citations